2023
DOI: 10.1302/0301-620x.105b9.bjj-2022-1437.r1
|View full text |Cite
|
Sign up to set email alerts
|

Delaying anterior cruciate ligament reconstruction increases the rate and severity of medial chondral injuries

Nicolas Cance,
Julien Erard,
Jobe Shatrov
et al.

Abstract: AimsThe aim of this study was to evaluate the association between chondral injury and interval from anterior cruciate ligament (ACL) tear to surgical reconstruction (ACLr).MethodsBetween January 2012 and January 2022, 1,840 consecutive ACLrs were performed and included in a single-centre retrospective cohort. Exclusion criteria were partial tears, multiligament knee injuries, prior ipsilateral knee surgery, concomitant unicompartmental knee arthroplasty or high tibial osteotomy, ACL agenesis, and unknown date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…ACL injury and its surgical reconstruction is known to increase inflammatory cytokines in the synovial fluid and cartilage breakdown biomarkers which, if not resolved in a timely manner, can lead to poor outcomes. 1 , 2 , 8 , 9 , 48 , 49 Despite sex-specific phenotypic and temporal differences in joint tissue healing profiles, we have shown that perioperative ALM therapy facilitates timely resolution of postoperative inflammation, leading to augmented joint tissue healing profiles in both males and females, 28 days after ACLR surgery. Local infiltration analgesia, commonly comprising lidocaine, is a safe and effective technique widely used by orthopaedic surgeons during ACLR surgery to minimize postoperative pain.…”
Section: Discussionmentioning
confidence: 83%
“…ACL injury and its surgical reconstruction is known to increase inflammatory cytokines in the synovial fluid and cartilage breakdown biomarkers which, if not resolved in a timely manner, can lead to poor outcomes. 1 , 2 , 8 , 9 , 48 , 49 Despite sex-specific phenotypic and temporal differences in joint tissue healing profiles, we have shown that perioperative ALM therapy facilitates timely resolution of postoperative inflammation, leading to augmented joint tissue healing profiles in both males and females, 28 days after ACLR surgery. Local infiltration analgesia, commonly comprising lidocaine, is a safe and effective technique widely used by orthopaedic surgeons during ACLR surgery to minimize postoperative pain.…”
Section: Discussionmentioning
confidence: 83%
“…In the current study, the incidence of MMLs increased in a time-dependent manner: 59.6% of patients with an injury to surgery time >12 months had an MML, compared with 38.7% of patients with an injury to surgery time of 3 to 12 months and only 33.1% with an injury to surgery time <3 months. Multiple previous studies, 1,5-8,16,19,24,34,42,43 with timelines ranging from 3 months to >5 years, have explored the association between concomitant intra-articular lesions and time between injury and ACLR, showing similar trends of increased incidence of MMLs. Tandogan et al 43 reported an odds ratio (OR) for MMLs of 2.2 with a time between index injury and surgery of 2 to 5 years and an OR of 5.9 with an interval >5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also reported by Dumont et al, 11 showing a strong correlation between meniscal lesions and the occurrence of chondral injury to the same compartment, especially at the medial femoral condyle. Moreover, numerous authors 5-7,16,42 have reported an association between increased injury to surgery time and chondral damage. Similarly, our results showed an increased incidence of chondral damage over time (6.1% and 15.6% with an injury to surgery time of <3 months and >12 months, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 - 6 In addition to the early physical and psychological morbidity, these injuries are also associated with increased risk of developing knee osteoarthritis in later life. 1 , 7 , 8 As the large majority of ACL injuries are sustained from a noncontact pivot injury, identifying risk factors and developing appropriate preventative strategies may help to reduce the burden of these injuries on the patient, sporting institution and healthcare system.…”
Section: Introductionmentioning
confidence: 99%